Good Governance: Characteristics, Methods and the Austrian Examples - Friederike Friederike BUNDSCHUH-RIESENEDER (Transylvanian Review of Administrative Sciences, 2008)
The paper defines the term “Governance” and explores its characteristics such as participation, legitimacy, transparency, effectiveness and efficiency or accountability. Furthermore, it contains the description of different methods such as Government Business Process Reengineering, Public Private Partnership, New Public Management or the Reform of Public Administration. Also the paper shows procedures and trends in Austria, for example the establishment of E-Government including its legislation and developments of the national infrastructure.